Hypoxia promotes pancreatic adenocarcinoma progression by stabilizing ID1 via TRIM21 suppression - Cheng, Rui; Tang, Yuanjun; Cao, Xuedi; Huang, Zhanya; Guo, Yunyun; Jin, Renjing; Wang, Yan; Liu, Yang; Xue, Lixiang; Wang, Yuqing (Frontiers in Oncology, 2025)
IntroductionPancreatic adenocarcinoma (PAAD) is a highly aggressive malignancy characterized by a profoundly hypoxic tumor microenvironment, which fosters tumor progression and confers resistance to therapy The oncogenic regulator ID1has been implicated in PAAD malignancy, however, the mechanisms underlying hypoxia-induced stabilization of ID1 and the role of ubiquitin-mediated degradation remain poorly understood. Elucidating these pathways is essential for identifying novel therapeutic targets for PAAD.MethodsIn this study, we examined ID1 expression in PAAD tissues and cell lines using publicly available databases and in vitro models. We simulated hypoxic conditions to assess their effects on ID1 expression and tumor cell behaviors, including proliferation, migration, and invasion. Protein stability was investigated via cycloheximide chase, proteasome and autophagy inhibition, and ubiquitination assays. Mass spectrometry identified TRIM21 as an E3 ubiquitin ligase interacting with ID1. To investigate its regulatory role, we generated stable TRIM21 knockdown and overexpression pancreatic cancer cell lines. Finally, in vivo xenograft experiments were conducted to evaluate the impact of ID1 and TRIM21 on tumor growth.ResultsID1 was markedly overexpressed in PAAD tissues and cell lines, correlating with advanced tumor stage, metastasis, and reduced patient survival. Hypoxia elevated ID1 protein levels without significantly affecting its mRNA, suggesting post-translational stabilization. Mechanistic studies revealed that hypoxia inhibits ubiquitin-proteasome-mediated degradation of ID1 by downregulating TRIM21, an E3 ubiquitin ligase responsible for ID1 ubiquitination. TRIM21 knockdown restored ID1 levels and promoted tumor cell function, whereas TRIM21 overexpression suppressed these malignant phenotypes and mitigated hypoxia-induced aggressiveness. In vivo, ID1 silencing impeded, while TRIM21 knockdown accelerated, pancreatic tumor growth, confirming their opposing roles in tumor progression.DiscussionOur findings demonstrate that hypoxia drives pancreatic tumor progression by downregulating TRIM21, leading to stabilization of the oncogenic protein ID1. The TRIM21–ID1 axis emerges as a promising therapeutic target for PAAD, suggesting that restoring TRIM21-mediated ID1 degradation could counteract hypoxia-induced malignancy.